Carbonation of fluidized bed combustion solids - Rao, Arjun Shankar (University of Ottawa (Canada), 2006)
Fluidized bed combustion (FBC) ash from the combustion of high-sulphur fuels with limestone addition can contain from 15 to 25% quick lime content. This excess calcium oxide gives the ash numerous undesirable properties such as strong exothermicity on wetting and high-pH leachate that must be treated before discharge. It also leads to the formation of ettringite with significant deleterious expansion in the landfill. In consequence, carbonation of FBC ash is desirable in order to reduce its alkalinity and improve its disposal characteristics. The current technique to reduce the exothermic character of the ash involves hydrating the ash in two stages, leading to the consumption of large quantities of water. Sonication along with simultaneous carbonation of the ash yields a product suitable for direct disposal in landfills with the minimum of water addition (to achieve the optimum proctor levels for maximum compaction of the ash in the landfill site). This work explores the use of sonochemical-enhanced carbonation of FBC ash. Tests have been conducted using four ashes, two of which differ in age only and are from the Nova Scotia Power 183 MWe CFBC (circulating fluidized bed combustor) boiler. The other two ashes are from the CFBC boilers at A/C power and Piney Creek, U.S.A. Tests with additives such as sodium chloride (at levels comparable with that in seawater) and seawater from Nova Scotia have also been carried out. Tests were carried out at low (20°, 40°C) and high (60°, 80°C) temperatures. Sonicated samples were also analyzed using TGA (Thermogravimetric analysis), TGA-FTIR (Thermogravimetric and Fourier transform infra red spectroscopy analysis) and XRD (X-ray diffraction) techniques to determine the influence of other calcium compounds (OCC). The size reduction brought about by sonication was quantified using wet sieving. The ash reactivity displays a strong temperature dependency with almost complete carbonation of the ashes being achieved in minutes at higher temperatures. Additives were found to increase the level of hydration of the ashes in line with previous work; however, carbonation levels were unaffected. TGA, TGA-FTIR and XRD analysis of the samples indicated that other calcium compounds (OCC) were also formed during hydration.
Keywords: Engineering, Chemical.